Effectiveness of Animated Cartoon Distraction on Pre-school Children's Anxiety during Infusion Insertion in the Emergency Room of RSUD Hajjah Andi Depu - Najamuddin, Nur Isriani; Gibran, Khalil (LPPM STIKes Muhammadiyah Ciamis, 2024)
Background: Anxiety in preschool children during hospital procedures is a common issue, particularly during invasive actions such as intravenous (IV) insertion. One non-pharmacological intervention to address this problem is animated cartoon audiovisual distraction, which serves to divert the child's attention and reduce perceived stress. Methods: This study aimed to examine the effect of animated cartoon audiovisual distraction on the anxiety levels of preschool children undergoing IV insertion. A quasi-experimental design with a pre-test post-test control group approach was employed. The sample consisted of 20 preschool children selected using purposive sampling. Data on anxiety levels were collected before and after the intervention and analyzed using the Wilcoxon Signed Ranks Test. Results: The results showed a statistically significant reduction in anxiety levels, with a p-value of 0.006, indicating that animated cartoon audiovisual distraction significantly reduced anxiety during IV insertion. Conclusion: These findings suggest that such distractions can be effectively integrated into emergency room procedures as a supportive, non-pharmacological strategy to minimize procedural anxiety in young children.